Allowed to lead? A qualitative investigation of the impact of the stained-glass labyrinth on women in pastoral leadership in the Evangelical Covenant Church - Reeves, Monica (My University, 2026)
This qualitative study investigated the experiences of women in pastoral leadership in the Evangelical Covenant Church, seeking to understand how they experience the stained-glass labyrinth and perceive ECC leadership amid their challenges (Lauve-Moon, 2021). A denomination that has ordained women since 1976, the ECC serves as a unique case study, and specific attention was given to its organization Advocates for Covenant Clergy Women. The ACCW seeks to come alongside women as they need support and to advocate for change. The group’s motto captures the challenges at the local church level, “until the culture of our churches matches the ethos of the denomination, we have work to do” (ACCW, Home, n.d.). To investigate the experiences of women in pastoral leadership in the ECC, the following research questions guided this study: RQ1: In what ways are women experiencing the stained-glass labyrinth (SGL) in the ECC? RQ2: What are participants’ perceptions of ECC leadership and their support of women? RQ3: How does the ACCW affect the experience of the SGL for women? Role congruity theory and feminist standpoint theory provided an effective theoretical framework to understand women’s experiences and consider how structure and culture impact the SGL. Guided by an interpretive and critical methodology, I conducted 38 interviews with women in the ECC who have served or currently serve in a pastoral leadership role, while also using a contextual reading of documents to examine ECC messaging. Findings point to how the ECC structure creates and supports continued problems for women. Many participants view the ECC’s commitment to a “freedom to disagree” as a strength of the denomination. But when misapplied, this tenet combined with a structure design that gives most power to the local level, women face additional obstacles in their leadership pursuits. With the local church level holding power to break from the ECC’s commitment to women in leadership, women face an impossible hurdle and instead are discouraged from pursuing pastoral jobs in certain regions or churches. In short, practice does not match policy and though this is a reality that many ECC leaders recognize, to date nothing has been done to hold churches accountable. This study focuses on the mental, emotional, and physical toll that the SGL has on women in pastoral leadership in the ECC. Participants shared mainly positive impressions of ECC national leadership, though they recognize that there are problems at the regional and local level. I argue that the weight of these burdens could be lessened greatly if the ECC functioned with consistency between their identity and policies and enforced their commitment to women at every level. The ACCW is a strong resource and though many participants were not familiar with everything they do, most spoke positively about its existence, and many discussed a desire to get more involved. However, the weight of this work should not fall on the women and men in the ACCW, but rather ECC leadership should work to be more consistent in its policy and practice.
Keywords: Stained-glass labyrinth; Women in leadership; Organizational communication; Policy-practice gap; Community-engaged research; Feminist orientation